2017
DOI: 10.1186/s41256-017-0054-7
|View full text |Cite
|
Sign up to set email alerts
|

Reasons to pursue a career in medicine: a qualitative study in Sierra Leone

Abstract: BackgroundMany low-income and crises-affected countries like Sierra Leone struggle with the recruitment and retention of their health professionals, particularly nurses and doctors. There are multiple factors that influence the ‘recruitment to retention’ pipeline. The first stage of an exploration into the issues influencing the availability of qualified health care workers may focus on the aspects which influence their entry into relevant educational programmes. This paper explores the reasons given by junior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Next, the fact that the 3rd and 4th motivations were "attractiveness of the medical profession and its characteristics" and "vocation" is rather a good thing, since researchers have shown that these motivations are associated with significant subsequent satisfaction in practice (Heikkilä et al, 2015). The category "vocation" has been found in other studies (Heikkilä et al, 2015;Wouters et al, 2017), and also seems to fit Woodward's « child's dream » category (Woodward et al, 2017). The 5 th category « social influence of a family member practicing medicine or a related profession » includes reasons also found in the qualitative study of Woodward et al: « inspired by role models » and « influence of family members ».…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Next, the fact that the 3rd and 4th motivations were "attractiveness of the medical profession and its characteristics" and "vocation" is rather a good thing, since researchers have shown that these motivations are associated with significant subsequent satisfaction in practice (Heikkilä et al, 2015). The category "vocation" has been found in other studies (Heikkilä et al, 2015;Wouters et al, 2017), and also seems to fit Woodward's « child's dream » category (Woodward et al, 2017). The 5 th category « social influence of a family member practicing medicine or a related profession » includes reasons also found in the qualitative study of Woodward et al: « inspired by role models » and « influence of family members ».…”
Section: Discussionmentioning
confidence: 88%
“…Students' interactions with medical staff have been implicated in the decline of the idealism students present towards their future profession (Morley et al, 2013). Some authors argue that if this "idealistic" motivation does not meet the practical experience, some students may feel disillusioned and may withdraw from medical education (Girasek et al, 2011;Woodward et al, 2017). One study showed that one-third of medical students would never do these studies again (Pruthi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, economic status and personal background are the reasons for students to choose medicine. Usually students choose medicine for various reasons such as global recognition, job opportunities abroad, status and respect in society, stability in employment, and job security (Newton et al, 1998;Woodward et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a lack of research evidence to back up or refute this belief. Although there have been past studies in other countries which question the motivation of students applying to study medicine, it was found that results vary across different countries or cultures (Woodward, Thomas, Jalloh, Rees, & Leather, 2017), thus further cementing the need to carry out this study.…”
Section: Types Of Motivation Extrinsic Motivationmentioning
confidence: 92%